PERANAN RISK-PREFERENCE TERHADAP PEMBIAYAAN MACET PADA BMT: METODE EKSPERIMEN MULTIPLE PRICE LIST - DAVY HENDRI (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2017)
The theme of the article is the banks and financial institutions. Several studies have also found that various LKMS financing products also provide incentives and disincentives to the trend of stalled installment financing. This study highlights the impact of characteristics such as: risk and religiosity preferences, which may differ from individual beneficiaries of financing to sharia microfinance institutions (LKMS) to the probability of stalling their financing. The study was conducted by taking primary data in the form of samples of 60 customers who received financing from 1 LKMS but consisted of 30 debtors who experienced financing installment defaults and 30 went smoothly. The process of collecting data uses a questionnaire containing questions about basic demographics, in addition to questions aimed at raising Islamic risk and religiosity preferences. In addition, the impact of external environmental characteristics is also estimated by using probit regression. Group-based financing, which is one of the objectives of reducing adverse selection, can have the opposite effect. Ineffective group roles for various reasons, contagion can be a trigger for moral hazard for other group members. The study found that in addition to religiosity, as an internal factor, the effectiveness of financing groups as a timely external factor of timely payment compliance also plays an important role.